Comparative Analysis Of Solar Panel Output Power Using Reflected Light And Direct Sunlight - Byancha Priscilla; Alfrie M. Rampengan; Arik S. Nugroho (Universitas Katolik Widya Karya Malang, 2023)
This study pertains to the utilization of solar energy as a sustainable energy source, which exhibits considerable promise in Indonesia. The average daily solar radiation intensity in Indonesia is estimated to be approximately 4.8 kWh/m2. Nevertheless, the practical implementation of the Solar Power Plant (PLTS) presents several problems, including the need to improve the output power efficiency of the solar panels. This aspect offers the potential for significant enhancement. This study aimed to evaluate the performance of solar modules when equipped with reflectors, through a comparative analysis. In order to enhance the output power of the solar module, it is vital to augment the solar radiation received by this module. Based on the data acquired, it can be observed that the utilization of reflectors within the time frame of 11.00-12.00 WIT yields the maximum efficiency value.